Preparation method and application of composite oxide carrier

By preparing a composite oxide support with rich microporous structure and high mechanical strength, the problem of inactivation of a single oxide support under high temperature and high pressure conditions is solved, the stability and catalytic activity of acetylene selective hydrogenation catalyst is improved, and the Efficient ethylene selectivity and efficient conversion of long-term reactions.

CN118384927BActive Publication Date: 2025-01-14ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410477367.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-19
Publication Date
2025-01-14
Estimated Expiration
2044-04-19

AI Technical Summary

Technical Problem

The structure of a single pure oxide support is unstable under high temperature and high pressure reaction conditions, resulting in catalyst deactivation, affecting the efficiency and stability of the selective hydrogenation reaction of acetylene.

Method used

By using the preparation method of composite oxide support, Al2O3 powder is mixed with other oxide powders (such as SiO2, TiO2, CeO2, etc.) and pore-forming agent, and then undergoes high temperature and high pressure molding and infrared heating treatment to form a rich micropore structure and high A composite oxide support with mechanical strength and the active metal Pd is supported by this support to prepare an acetylene selective hydrogenation catalyst.

Benefits of technology

The stability and catalytic activity of the catalyst are improved, the acetylene conversion rate can reach more than 97%, the ethylene selectivity can reach more than 80%, and the efficient activity is maintained during long-term reactions, which significantly improves the durability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004800896660000101
    Figure BDA0004800896660000101
  • Figure BDA0004800896660000111
    Figure BDA0004800896660000111
  • Figure BDA0004800896660000112
    Figure BDA0004800896660000112
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of a composite oxide carrier, the preparation method comprising the following steps: Step 1): taking Al2O3 powder and M x O y The powder and the pore-forming agent are mixed uniformly; step 2): the uniform mixture is put into a bag and vacuumized; step 3): the bag is vacuum-sealed and placed in a heating reactor, and the reactor is sealed and filled with inert gas, and molding and sintering are completed under the combined action of high temperature and high pressure; step 4): after the heating reactor is cooled to room temperature, the bag is removed to obtain a composite oxide molded product; step 5): the molded product is placed in an infrared heater for heating; step 6): the molded product treated in step 5) is crushed to obtain composite oxide carrier particles. The present invention provides an application of the prepared composite oxide carrier in the preparation of a catalyst for the selective hydrogenation of acetylene, and the catalyst can achieve high acetylene conversion, high ethylene selectivity and good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to application of a preparation method of a composite oxide carrier in preparing an acetylene selective hydrogenation catalyst. Background Art

[0002] Ethylene is a substance widely used in daily life and industrial production. As a raw material for many commodities such as solvents, pharmaceuticals, textile fibers and plastics, it plays a key role in the development of many industries. Ethylene plays an important role in the chemical industry, and the advanced level of its production technology is regarded as an important indicator of a country's petrochemical development level. At present, most ethylene is produced through the petroleum cracking process, which produces a small amount of acetylene, which has an adverse effect on the catalyst in the ethylene polymerization process, thereby affecting the quality of the final product. Therefore, effective methods must be taken to remove acetylene. At present, common methods for removing acetylene include solvent adsorption, catalytic hydrogenation, low-temperature ketone precipitation, amination and complex absorption. Among them, the selective hydrogenation of acetylene is widely used in industrial production because of its advantages such as simple operation, less pollution, low energy consumption, and the ability to improve the recovery rate of ethylene.

[0003] In the selective hydrogenation of acetylene, the commonly used catalyst is a supported catalyst composed of a metal active substance and a carrier. The active component has the greatest impact on the performance of the catalyst in the chemical reaction, but the carrier is also a crucial component of the catalyst. The carrier not only provides a substrate with sufficient mechanical strength and pore structure for the catalyst to load the active metal components, improves the dispersion of metal particles, but also inhibits the agglomeration phenomenon during the reaction. At the same time, the physical properties, pH value of the carrier, and the interaction between the active metal and the carrier can affect the catalytic performance. At present, the common catalyst carriers are mainly traditional inorganic oxide carriers and carbon carriers. In addition, some new carriers such as metal-organic frameworks (MOFs) have also become a hot topic of research. Inorganic oxide carriers are the most commonly used carrier type in industrial acetylene selective hydrogenation catalysts. This type of carrier can usually be divided into two categories: one is a carrier with no catalytic activity, such as Al2O3 and SiO2, whose main function is to disperse metal particles and is not reducible, so they are called inert carriers. The other type is a reducing carrier that can both disperse active metal components and participate in electron transfer and activation in catalytic reactions, including TiO2 and CeO2. In practical applications, inorganic oxide carriers are widely used in various catalysts due to their excellent stability and dispersibility. In particular, in the selective hydrogenation of acetylene, inorganic oxide carriers can effectively disperse active metal components, thereby making the catalyst have good catalytic activity. However, the catalyst prepared with a single oxide carrier is structurally unstable under high temperature and high pressure reaction conditions, which may cause the matrix structure to collapse and lead to catalyst deactivation. Therefore, there is a broad space for development in the research of inorganic oxide carriers. This type of technology urgently needs to be broken through to provide more possibilities for the design and optimization of catalysts.

[0004] Based on the above background, it is necessary to develop an improved catalyst carrier and design a composite oxide carrier that can provide high temperature resistance and structural stability for use in acetylene selective hydrogenation catalysts, thereby facilitating the industrial production of ethylene. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of catalyst deactivation and poor catalyst stability caused by the collapse of the matrix structure of a single pure oxide carrier in the existing acetylene selective hydrogenation catalyst under high temperature reaction conditions, and to provide a method for preparing a composite oxide carrier and the application of the composite oxide carrier in preparing an acetylene selective hydrogenation catalyst; the catalyst prepared by using the composite oxide carrier can achieve a higher acetylene conversion rate and a higher ethylene selectivity in the acetylene selective hydrogenation to ethylene reaction, and the catalyst has good stability.

[0006] The technical solution adopted by the present invention is described in detail below.

[0007] In a first aspect, the present invention provides a method for preparing a composite oxide carrier, comprising the following steps:

[0008] Step 1): Take Al2O3 powder and M x O y powder and pore-forming agent, and mix them uniformly; the M x O y One or more selected from SiO2, CaO, TiO2, CeO2, Fe2O3, BaO; the Al2O3 powder and M x O y The mass ratio of powder to pore-forming agent is 10-40:10-30:1;

[0009] Step 2): the uniform mixture of step 1) is placed in a bag, and the gas adsorbed on the powder surface, the gaps between the powders and the bag is removed by vacuum operation;

[0010] Step 3): vacuum seal the package and place it in a heated reactor, seal the reactor and fill it with inert gas to a pressure of 200-400 bar, then heat it to 200-500° C., keep it warm for 4-8 hours, and complete molding and sintering under the combined action of high temperature and high pressure;

[0011] Step 4): after the heated reactor is cooled to room temperature, the sheath is removed to obtain a composite oxide formed object, the shape of which is consistent with the shape of the inner cavity of the sheath;

[0012] Step 5): placing the molded product obtained in step 4) in an infrared heater for heating at a temperature of 100 to 600° C. for a holding time of 10 to 15 hours;

[0013] Step 6): The molded product treated in step 5) is crushed to obtain composite oxide carrier particles of a desired mesh size.

[0014] The composite oxide carrier has a rich microporous structure and a specific surface area of ​​390 to 419 m 2 / g, the bulk density can reach 0.62-0.74g / mL, and the pore volume can reach 0.73-0.84mL / g; the composite oxide carrier has good thermal stability, which can prevent the temperature difference from damaging the material, prevent elastic deformation and damage caused by high temperature, and the compressive strength can reach 42-50N / cm 2 .

[0015] The Al2O3 powder and M x O y All powders were purchased from commercial sources.

[0016] Furthermore, the pore-forming agent in step 1) is selected from one or more of ammonium carbonate, ammonium bicarbonate, ammonium chloride and urea.

[0017] Further, in step 1) the Al2O3 powder and M x O y The mass ratio of powder to pore-forming agent is 10-30:10-30:1, preferably 20:20:1.

[0018] Further, in step 2), the vacuum degree in the package is 10 -1 ~10 -3 Pa, preferably the vacuum degree is 10 -1 Pa. Furthermore, the vacuum pumping parameters are set as follows: the pumping rate is 10 mL / s.

[0019] Furthermore, the pressure in the heating reactor in step 3) is 200 bar.

[0020] Furthermore, the inert gas introduced in step 3) is N2 or Ar.

[0021] Furthermore, the mesh size of the composite oxide carrier particles obtained after pulverization in step 6) is 60 to 80 meshes. Furthermore, the pulverization is performed using a jet mill, and the parameters are set as follows: installed power of 147kw, air consumption of 20L / min, air pressure of 0.7 to 0.85MPa, preferably 0.7MPa.

[0022] In a second aspect, the present invention provides use of a composite oxide support prepared according to the preparation method described in the first aspect in preparing a catalyst for the selective hydrogenation of acetylene.

[0023] Furthermore, the active component of the acetylene selective hydrogenation reaction catalyst is Pd.

[0024] Furthermore, the acetylene selective hydrogenation reaction catalyst is prepared by the following method: the composite oxide support is impregnated in a Pd precursor solution, the active material is fully adsorbed on the support, and then dried and reduced with hydrogen to obtain the acetylene selective hydrogenation reaction catalyst, which is denoted as Pd / Al2O3-M x O y catalyst.

[0025] Furthermore, the precursor of Pd is PdCl2. The PdCl2 is generally dissolved in dilute hydrochloric acid to form H2[PdCl4].

[0026] In a third aspect, the present invention provides an application of an acetylene selective hydrogenation reaction catalyst obtained according to the application described in the second aspect in an acetylene selective hydrogenation reaction, wherein the acetylene selective hydrogenation reaction catalyst uses the composite oxide support described in the first aspect as a support.

[0027] The specific application steps of the acetylene selective hydrogenation reaction catalyst in the acetylene selective hydrogenation reaction are: in a fixed bed reactor, the acetylene selective hydrogenation reaction catalyst prepared by the carrier is loaded, raw gas containing acetylene and hydrogen is introduced, the reaction temperature is set to 160-200° C., the reaction pressure is set to 0.1-0.5 MPa, and ethylene is generated by reaction.

[0028] Furthermore, the ratio of the amount of gas substances in the raw material gas is n(H2):n(C2H2)=2:1. The raw material gas generally also contains ethylene and nitrogen (as a carrier gas).

[0029] Furthermore, the acetylene gas space velocity is 6000~10000h -1 .

[0030] The catalyst prepared by the composite oxide carrier loaded with active metals of the present invention has good mechanical strength and stability, and has good catalytic activity in the above-mentioned selective hydrogenation of acetylene to ethylene reaction, the acetylene conversion rate can reach up to more than 97%, the ethylene selectivity can reach up to more than 80%, and a long-term reaction can be achieved. After the reaction for 500 hours, the acetylene conversion rate is still maintained at about 85%, and the ethylene selectivity is about 90%.

[0031] Compared with the prior art, the present invention has the following innovations and technical advantages:

[0032] (1) The composite oxide carrier prepared by the present invention has a large specific surface area, a low bulk density, a high pore volume, and a rich microporous structure, which is conducive to loading metal oxides. It has high mechanical strength and excellent thermal stability.

[0033] (2) The acetylene selective hydrogenation reaction catalyst prepared by the present invention using the composite oxide carrier has high catalytic activity, good ethylene selectivity, and excellent catalytic stability, and can maintain high catalytic activity for a long time.

[0034] (2) The present invention adopts hot isostatic pressing process to synthesize the composite oxide carrier, which can be formed and sintered at a relatively low temperature, has good material uniformity, short production cycle, low energy consumption, and high cost-effectiveness.

[0035] (3) The present invention uses an infrared heater for heat treatment, which has a gentle heating method, provides precise temperature control, achieves local heating, and has high heating efficiency.

[0036] (4) The present invention uses a jet mill for pulverization, and the pulverized product has good particle shape, narrow particle size distribution, less dust, low noise, and a clean and environmentally friendly production process. DETAILED DESCRIPTION

[0037] The present invention is described below with specific examples. It is necessary to point out that the examples are only used to further illustrate the present invention, but cannot be understood as limiting the scope of protection of the present invention, and the present invention is not limited thereto in any way. Those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.

[0038] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.

[0039] The 0.001 g / mL PdCl2 solution in the examples and comparative examples is prepared by dissolving in 0.3 M dilute hydrochloric acid and then adding deionized water, where 0.001 g / mL refers to the concentration of Pd.

[0040] The sources of some of the oxides used in the embodiments and comparative examples are as follows:

[0041] SiO2: Shandong Yunxin New Material Technology Co., Ltd., CAS: 7631-86-9, grade: industrial grade;

[0042] Al2O3: γ-Al2O3, purchased from Yangzhou Zhongtianli New Materials Co., Ltd., CAS No.: 1344-28-1, white powder, specific surface area 300m 2 / g;

[0043] Calcium oxide: Hebei Huihao Environmental Protection Technology Co., Ltd., CAS: 1305-78-8, white powder, industrial grade;

[0044] Barium oxide: Jiangsu Pules Biotechnology Co., Ltd., CAS: 1304-28-5, superior product;

[0045] Cerium oxide: Wo Nai Xi New Materials, CAS: 1036-38-3, light yellow powder, qualified product.

[0046] Example 1

[0047] Step 1) Weigh 20 g of Al2O3 powder, 20 g of SiO2 powder, and 1 g of ammonium carbonate, and mix them evenly;

[0048] Step 2) The uniform mixture of step 1) is placed in a bag, and the gas adsorbed on the powder surface, the gap between powders and the bag is evacuated at a pumping rate of 10 mL / s to make the vacuum degree reach 10 -1Pa;

[0049] Step 3) The package is vacuum sealed and placed in a heated reactor. After the reactor is sealed, N2 is filled to make the pressure in the reactor reach 200 bar, and then the temperature is raised to 200° C. and maintained at the temperature for 8 hours to complete the molding and sintering under the combined action of high temperature and high pressure;

[0050] Step 4) After the reaction kettle is cooled to room temperature, the sheath is removed to obtain a composite oxide molded product, which is in the shape of a cuboid with a length of 4 cm, a width of 2 cm, and a height of 2 cm;

[0051] Step 5) placing the molded product obtained in step 4) in an infrared heater for heating at a temperature of 100° C. for 10 h;

[0052] Step 6) The molded product after the heat treatment in step 5) is crushed in a jet mill with an installed power of 147 kW, an air consumption of 20 L / min, and an air pressure of 0.7 MPa to obtain composite oxide carrier particles of 60 to 80 mesh;

[0053] The structural performance of the above carrier was tested, and the specific surface area of ​​the carrier was measured by nitrogen physical adsorption BET method to be 400m 2 / g, the bulk density was calculated by measuring the mass of 10mL of the carrier to be 0.67g / mL, the pore volume of the carrier was measured by mercury intrusion method to be 0.79mL / g, and the compressive strength of the carrier was measured by compression test method to be 45N / cm 2 .

[0054] Example 2

[0055] Step 1) Weigh 20 g of Al2O3 powder, 20 g of CaO powder, and 1 g of ammonium bicarbonate, and mix them evenly;

[0056] Step 2) The uniform mixture of step 1) is placed in a bag, and the gas adsorbed on the powder surface, the gap between powders and the bag is evacuated at a pumping rate of 10 mL / s to make the vacuum degree reach 10 -1 Pa;

[0057] Step 3) The package is vacuum sealed and placed in a heated reactor. After the reactor is sealed, N2 is filled to make the pressure in the reactor reach 200 bar, and then the temperature is raised to 300°C and maintained for 6 hours to complete the molding and sintering under the combined action of high temperature and high pressure;

[0058] Step 4) After the reaction kettle is cooled to room temperature, the sheath is removed to obtain a composite oxide molded product, which is in the shape of a cuboid with a length of 4 cm, a width of 2 cm, and a height of 2 cm;

[0059] Step 5) placing the molded product obtained in step 4) in an infrared heater for heating at a temperature of 200° C. for a heating time of 12 h;

[0060] Step 6) The molded product after the heat treatment in step 5) is crushed in a jet mill with an installed power of 147 kW, an air consumption of 20 L / min, and an air pressure of 0.7 MPa to obtain composite oxide carrier particles of 60 to 80 mesh;

[0061] The structural performance of the above carrier was tested, and the specific surface area of ​​the carrier was measured by nitrogen physical adsorption BET method to be 409m 2 / g, the bulk density was calculated by measuring the mass of 10mL of the carrier to be 0.69g / mL, the pore volume of the carrier was measured by mercury intrusion method to be 0.80mL / g, and the compressive strength of the carrier was measured by compression test method to be 47N / cm 2 .

[0062] Example 3

[0063] Step 1) Weigh 20 g of Al2O3 powder, 20 g of TiO2 powder, and 1 g of urea, and mix them evenly;

[0064] Step 2) The uniform mixture of step 1) is placed in a bag, and the gas adsorbed on the powder surface, the gap between powders and the bag is evacuated at a pumping rate of 10 mL / s to make the vacuum degree reach 10 -1 Pa;

[0065] Step 3) The package is vacuum sealed and placed in a heated reactor. After the reactor is sealed, N2 is filled to make the pressure in the reactor reach 200 bar, and then the temperature is raised to 400°C and maintained for 4 hours to complete the molding and sintering under the combined action of high temperature and high pressure;

[0066] Step 4) After the reaction kettle is cooled to room temperature, the sheath is removed to obtain a composite oxide molded product, which is in the shape of a cuboid with a length of 4 cm, a width of 2 cm, and a height of 2 cm;

[0067] Step 5) placing the molded product obtained in step 4) in an infrared heater for heating at a temperature of 400° C. for a heating time of 14 h;

[0068] Step 6) The molded product after the heat treatment in step 5) is crushed in a jet mill with an installed power of 147 kW, an air consumption of 20 L / min, and an air pressure of 0.7 MPa to obtain composite oxide carrier particles of 60 to 80 mesh;

[0069] The structural performance of the above carrier was tested, and the specific surface area of ​​the carrier was measured by nitrogen physical adsorption BET method to be 415m 2 / g, the bulk density was calculated by measuring the mass of 10mL of the carrier to be 0.71g / mL, the pore volume of the carrier was measured by mercury intrusion method to be 0.81mL / g, and the compressive strength of the carrier was measured by compression test method to be 48N / cm 2 .

[0070] Example 4

[0071] Step 1) Weigh 20 g of Al2O3 powder, 20 g of CeO2 powder, and 1 g of urea, and mix them evenly;

[0072] Step 2) The uniform mixture of step 1) is placed in a bag, and the gas adsorbed on the powder surface, the gap between powders and the bag is evacuated at a pumping rate of 10 mL / s to make the vacuum degree reach 10 -1 Pa;

[0073] Step 3) The package is vacuum sealed and placed in a heated reactor. After the reactor is sealed, Ar is filled to make the pressure in the reactor reach 200 bar, and then the temperature is raised to 300° C. and maintained at the temperature for 5 hours to complete the molding and sintering under the combined action of high temperature and high pressure;

[0074] Step 4) After the reaction kettle is cooled to room temperature, the sheath is removed to obtain a composite oxide molded product, which is in the shape of a cuboid with a length of 4 cm, a width of 2 cm, and a height of 2 cm;

[0075] Step 5) placing the molded product obtained in step 4) in an infrared heater for heating at a temperature of 600° C. for 15 h;

[0076] Step 6) The molded product after the heat treatment in step 5) is crushed in a jet mill with an installed power of 147 kW, an air consumption of 20 L / min, and an air pressure of 0.7 MPa to obtain composite oxide carrier particles of 60 to 80 mesh;

[0077] The structural performance of the above carrier was tested, and the specific surface area of ​​the carrier was measured by nitrogen physical adsorption BET method to be 419m 2 / g, the bulk density was calculated by measuring the mass of 10mL of the carrier to be 0.74g / mL, the pore volume of the carrier was measured by mercury intrusion method to be 0.84mL / g, and the compressive strength of the carrier was measured by compression test method to be 50N / cm 2 .

[0078] Example 5

[0079] Step 1) Weigh 20 g of Al2O3 powder, 20 g of Fe2O3 powder, and 1 g of ammonium bicarbonate, and mix them evenly;

[0080] Step 2) The uniform mixture of step 1) is placed in a bag, and the gas adsorbed on the powder surface, the gap between powders and the bag is evacuated at a pumping rate of 10 mL / s to make the vacuum degree reach 10 -1 Pa;

[0081] Step 3) The package is vacuum sealed and placed in a heated reactor. After the reactor is sealed, Ar is filled to make the pressure in the reactor reach 200 bar, and then the temperature is raised to 400° C. and maintained for 4 hours to complete the molding and sintering under the combined action of high temperature and high pressure;

[0082] Step 4) After the reaction kettle is cooled to room temperature, the sheath is removed to obtain a composite oxide molded product, which is in the shape of a cuboid with a length of 4 cm, a width of 2 cm, and a height of 2 cm;

[0083] Step 5) placing the molded product obtained in step 4) in an infrared heater for heating at a temperature of 100° C. for 10 h;

[0084] Step 6) The molded product after the heat treatment in step 5) is crushed in a jet mill with an installed power of 147 kW, an air consumption of 20 L / min, and an air pressure of 0.7 MPa to obtain composite oxide carrier particles of 60 to 80 mesh;

[0085] The structural performance of the above carrier was tested, and the specific surface area of ​​the carrier was measured by nitrogen physical adsorption BET method to be 393m 2 / g, the bulk density was calculated by measuring the mass of 10mL of the carrier to be 0.65g / mL, the pore volume of the carrier was measured by mercury intrusion method to be 0.76mL / g, and the compressive strength of the carrier was measured by compression test method to be 43N / cm 2 .

[0086] Example 6

[0087] Step 1) Weigh 20 g of Al2O3 powder, 20 g of BaO powder, and 1 g of urea, and mix them evenly;

[0088] Step 2) The uniform mixture of step 1) is placed in a bag, and the gas adsorbed on the powder surface, the gap between powders and the bag is evacuated at a pumping rate of 10 mL / s to make the vacuum degree reach 10 -1 Pa;

[0089] Step 3) The package is vacuum sealed and placed in a heated reactor. After the reactor is sealed, N2 is filled to make the pressure in the reactor reach 200 bar, and then the temperature is raised to 500°C and maintained for 4 hours to complete the molding and sintering under the combined action of high temperature and high pressure;

[0090] Step 4) After the reaction kettle is cooled to room temperature, the sheath is removed to obtain a composite oxide molded product, which is in the shape of a cuboid with a length of 4 cm, a width of 2 cm, and a height of 2 cm;

[0091] Step 5) placing the molded product obtained in step 4) in an infrared heater for heating at a temperature of 500° C. for a heating time of 12 h;

[0092] Step 6) The molded product after the heat treatment in step 5) is crushed in a jet mill with an installed power of 147 kW, an air consumption of 20 L / min, and an air pressure of 0.7 MPa to obtain composite oxide carrier particles of 60 to 80 mesh;

[0093] The structural performance of the above carrier was tested, and the specific surface area of ​​the carrier was measured by nitrogen physical adsorption BET method to be 390m 2 / g, the bulk density was calculated by measuring the mass of 10mL of the carrier to be 0.62g / mL, the pore volume of the carrier was measured by mercury intrusion method to be 0.73mL / g, and the compressive strength of the carrier was measured by compression test method to be 42N / cm 2 .

[0094] Example 7

[0095] Step 1) Weigh 10 g of Al2O3 powder, 30 g of SiO2 powder, and 1 g of ammonium carbonate, and mix them evenly;

[0096] Step 2) The uniform mixture of step 1) is placed in a bag, and the gas adsorbed on the powder surface, the gap between powders and the bag is evacuated at a pumping rate of 10 mL / s to make the vacuum degree reach 10 -1 Pa;

[0097] Step 3) The package is vacuum sealed and placed in a heated reactor. After the reactor is sealed, N2 is filled to make the pressure in the reactor reach 200 bar, and then the temperature is raised to 200° C. and maintained at the temperature for 8 hours to complete the molding and sintering under the combined action of high temperature and high pressure;

[0098] Step 4) After the reaction kettle is cooled to room temperature, the sheath is removed to obtain a composite oxide molded product, which is in the shape of a cuboid with a length of 4 cm, a width of 2 cm, and a height of 2 cm;

[0099] Step 5) placing the molded product obtained in step 4) in an infrared heater for heating at a temperature of 100° C. for 10 h;

[0100] Step 6) The molded product after the heat treatment in step 5) is crushed in a jet mill with an installed power of 147 kW, an air consumption of 20 L / min, and an air pressure of 0.7 MPa to obtain composite oxide carrier particles of 60 to 80 mesh;

[0101] The structural performance of the above carrier was tested, and the specific surface area of ​​the carrier was measured by nitrogen physical adsorption BET method to be 398m 2 / g, the bulk density was calculated by measuring the mass of 10mL of the carrier to be 0.66g / mL, the pore volume of the carrier was measured by mercury intrusion method to be 0.78mL / g, and the compressive strength of the carrier was measured by compression test method to be 44N / cm 2 .

[0102] Example 8

[0103] Step 1) Weigh 30 g of Al2O3 powder, 10 g of SiO2 powder, and 1 g of ammonium carbonate, and mix them evenly;

[0104] Step 2) The uniform mixture of step 1) is placed in a bag, and the gas adsorbed on the powder surface, the gap between powders and the bag is evacuated at a pumping rate of 10 mL / s to make the vacuum degree reach 10 -1 Pa;

[0105] Step 3) The package is vacuum sealed and placed in a heated reactor. After the reactor is sealed, N2 is filled to make the pressure in the reactor reach 200 bar, and then the temperature is raised to 200° C. and maintained at the temperature for 8 hours to complete the molding and sintering under the combined action of high temperature and high pressure;

[0106] Step 4) After the reaction kettle is cooled to room temperature, the sheath is removed to obtain a composite oxide molded product, which is in the shape of a cuboid with a length of 4 cm, a width of 2 cm, and a height of 2 cm;

[0107] Step 5) placing the molded product obtained in step 4) in an infrared heater for heating at a temperature of 100° C. for 10 h;

[0108] Step 6) The molded product after the heat treatment in step 5) is crushed in a jet mill with an installed power of 147 kW, an air consumption of 20 L / min, and an air pressure of 0.7 MPa to obtain composite oxide carrier particles of 60 to 80 mesh;

[0109] The structural performance of the above carrier was tested, and the specific surface area of ​​the carrier was measured by nitrogen physical adsorption BET method to be 401m 2 / g, the bulk density was calculated by measuring the mass of 10mL of the carrier to be 0.68g / mL, the pore volume of the carrier was measured by mercury intrusion method to be 0.80mL / g, and the compressive strength of the carrier was measured by compression test method to be 46N / cm 2 .

[0110] The structural properties of the composite oxide supports prepared in different embodiments are summarized in Table 1.

[0111] Example 9

[0112] Example 9 uses the composite oxide carrier prepared in Example 1 to load 1 wt% of active metal Pd by an equal volume impregnation method to prepare a Pd-based catalyst, which is applied to the selective hydrogenation reaction of acetylene to evaluate the catalytic performance of the catalyst.

[0113] Step 1) Weigh 5 g of the composite oxide support prepared in Example 1 and 8.33 mL of a 0.001 g / mL PdCl2 solution;

[0114] Step 2) Immersing the composite oxide support of step 1) in a PdCl2 solution at room temperature for 12 hours to allow the active material to be fully adsorbed on the support;

[0115] Step 3) After the catalyst in step 2) is impregnated, it is placed in an oven to dry at a drying temperature of 110° C. for 12 h;

[0116] Step 4) After step 3) drying, the catalyst is placed in a hydrogen atmosphere for reduction operation at a reduction temperature of 170°C. After reduction for 2 hours, Pd / Al2O3-SiO2 is obtained;

[0117] The catalyst was evaluated for its catalytic performance in the selective hydrogenation of acetylene in a fixed bed reactor. The Pd / Al2O3-SiO2 catalyst prepared by the above method was loaded into the reactor, and a mixed gas consisting of 0.33% acetylene, 0.66% H2 and 33% ethylene (nitrogen as carrier gas) was introduced at a flow rate of 30 mL / min. The reaction temperature was 160°C and the acetylene space velocity was 6000 h -1 At the beginning of the reaction, the acetylene conversion rate was 97.2% and the ethylene selectivity was 94.1%. After 500 hours of reaction, the acetylene conversion rate was 85.1% and the ethylene selectivity was 90.5%. After the reaction, the catalyst bed position remained basically unchanged, indicating that the catalyst structure was very stable.

[0118] Comparative Example 1

[0119] Comparative Example 1 is to prepare a Pd-based catalyst by using a commercially purchased Al2O3 carrier to load 1 wt% of active metal Pd by an equal volume impregnation method, and apply it to the selective hydrogenation reaction of acetylene to evaluate the catalytic performance of the catalyst.

[0120] Step 1) Weigh 5 g of commercially purchased Al2O3 carrier and 8.33 mL of 0.001 g / mL PdCl2 solution;

[0121] Step 2) Immersing the composite oxide support of step 1) in a PdCl2 solution at room temperature for 12 hours to allow the active material to be fully adsorbed on the support;

[0122] Step 3) After the catalyst in step 2) is impregnated, it is placed in an oven to dry at a drying temperature of 110° C. for 12 h;

[0123] Step 4) After step 3) drying, the catalyst is placed in a hydrogen atmosphere for reduction operation at a reduction temperature of 170°C. After reduction for 2 hours, Pd / Al2O3 is obtained;

[0124] The catalyst was evaluated for its catalytic performance in the selective hydrogenation of acetylene in a fixed bed reactor. The Pd / Al2O3 catalyst prepared by the above method was loaded into the reactor, and a mixed gas consisting of 0.33% acetylene, 0.66% H2 and 33% ethylene (nitrogen as carrier gas) was introduced at a flow rate of 30 mL / min. The reaction temperature was 160°C and the acetylene space velocity was 6000 h -1 At the beginning of the reaction, the acetylene conversion rate was 96.7% and the ethylene selectivity was 92.3%. After 100 hours of reaction, the acetylene conversion rate was 56.8% and the ethylene selectivity was 93.2%. After the reaction, it was found that the catalyst bed height decreased slightly, indicating that the catalyst may have matrix collapse.

[0125] By comparing Example 9 with Comparative Example 1, it can be seen that the Pd-based catalyst prepared with the composite oxide carrier has a higher acetylene conversion rate and ethylene selectivity, and can maintain high catalytic activity for a long period of time, which significantly improves the catalytic stability of the catalyst.

[0126] Comparative Example 2

[0127] Comparative Example 2 is to prepare a Pd-based catalyst by using commercially available silicon dioxide as a carrier and loading 1 wt% of active metal Pd by an equal volume impregnation method. The catalyst is applied to the selective hydrogenation reaction of acetylene to evaluate the catalytic performance of the catalyst.

[0128] Step 1) Weigh 5 g of commercially purchased SiO2 carrier and 8.33 mL of 0.001 g / mL PdCl2 solution;

[0129] Step 2) Immersing the composite oxide support of step 1) in a PdCl2 solution at room temperature for 12 hours to allow the active material to be fully adsorbed on the support;

[0130] Step 3) After the catalyst in step 2) is impregnated, it is placed in an oven to dry at a drying temperature of 110° C. for 12 h;

[0131] Step 4) After step 3) drying, the catalyst is placed in a hydrogen atmosphere for reduction operation at a reduction temperature of 170°C. After reduction for 2 hours, Pd / SiO2 is obtained;

[0132] The catalyst was evaluated for its catalytic performance in the selective hydrogenation of acetylene in a fixed bed reactor. The Pd / SiO2 catalyst prepared by the above method was loaded into the reactor, and a mixed gas consisting of 0.33% acetylene, 0.66% H2 and 33% ethylene (nitrogen as carrier gas) was introduced at a flow rate of 30 mL / min. The reaction temperature was 160° C. and the acetylene space velocity was 6000 h -1 At the beginning of the reaction, the acetylene conversion was 20.3% and the ethylene selectivity was 93.5%.

[0133] Compared with Comparative Example 1, the initial catalytic activity of the Pd / SiO2 catalyst in Comparative Example 2 is very low, indicating that SiO2 alone as a carrier is not effective in loading the active substance Pd, resulting in poor catalytic activity.

[0134] Comparative Example 3:

[0135] Step 1) Weigh 40 g of Al2O3 powder and 1 g of ammonium carbonate and mix them evenly;

[0136] Step 2) The uniform mixture of step 1) is placed in a bag, and the gas adsorbed on the powder surface, the gap between powders and the bag is evacuated at a pumping rate of 10 mL / s to make the vacuum degree reach 10 -1 Pa;

[0137] Step 3) The package is vacuum sealed and placed in a heated reactor. After the reactor is sealed, N2 is filled to make the pressure in the reactor reach 200 bar, and then the temperature is raised to 200° C. and maintained at the temperature for 8 hours to complete the molding and sintering under the combined action of high temperature and high pressure;

[0138] Step 4) After the reactor is cooled to room temperature, the cover is removed to obtain an oxide molding, which is a rectangular parallelepiped with a length of 4 cm, a width of 2 cm, and a height of 2 cm;

[0139] Step 5) placing the molded product obtained in step 4) in an infrared heater for heating at a temperature of 100° C. for 10 h;

[0140] Step 6) The molded product after the heat treatment in step 5) is crushed in a jet mill with an installed power of 147 kW, an air consumption of 20 L / min, and an air pressure of 0.7 MPa to obtain oxide carrier particles of 60 to 80 mesh;

[0141] Step 7) Weigh 5 g of the oxide support prepared in step 6) and 8.33 mL of 0.001 g / mL PdCl2 solution;

[0142] Step 8) Immersing the oxide support from step 7) in a PdCl2 solution at room temperature for 12 hours to allow the active material to be fully adsorbed on the support;

[0143] Step 9) After the catalyst is impregnated in step 8), it is placed in an oven to dry at a drying temperature of 110° C. for 12 h;

[0144] Step 10) After step 9) drying, the catalyst is placed in a hydrogen atmosphere for reduction operation at a reduction temperature of 170°C. After reduction for 2 hours, Pd / Al2O3 is obtained;

[0145] The catalyst was evaluated for its catalytic performance in the selective hydrogenation of acetylene in a fixed bed reactor. The Pd / Al2O3 catalyst prepared by the above method was loaded into the reactor, and a mixed gas consisting of 0.33% acetylene, 0.66% H2 and 33% ethylene (nitrogen as carrier gas) was introduced at a flow rate of 30 mL / min. The reaction temperature was 160°C and the acetylene space velocity was 6000 h -1 At the initial stage of the reaction, the acetylene conversion rate was 94.6% and the ethylene selectivity was 92.6%. After 300 hours of reaction, the acetylene conversion rate was 62.4% and the ethylene selectivity was 91.3%.

[0146] Compared with Example 9, the initial catalytic activity of the Pd / Al2O3 catalyst in Comparative Example 3 is relatively good, but the catalytic activity of the Pd / Al2O3 catalyst in Comparative Example 3 decreases significantly after 300 hours, indicating that the thermal stability of the composite moldings of different oxides is better than that of a single oxide, and the structure is more stable.

[0147] Table 1. Structural properties of composite oxide supports prepared in different embodiments

[0148]

[0149]

[0150] Table 2. Catalytic performance of the catalysts prepared in Example 9 and Comparative Examples 1-3

[0151]

Claims

1. A method for preparing a composite oxide support for preparing an acetylene selective hydrogenation catalyst, characterized in that: The preparation method of the composite oxide carrier comprises the following steps: Step 1): Take Al2O3 powder and M x O y powder and pore-forming agent, and mix them uniformly; the M x O y One or more selected from SiO2, CaO, TiO2, CeO2, Fe2O3, BaO; the Al2O3 powder and M x O y The mass ratio of powder to pore-forming agent is 10-40:10-30:1; Step 2): the uniform mixture of step 1) is placed in a bag, and the gas adsorbed on the powder surface, the gaps between the powders and the bag is removed by vacuum operation; Step 3): vacuum seal the package and place it in a heated reactor, seal the reactor and fill it with inert gas to a pressure of 200-400 bar, then heat it to 200-500° C., keep it warm for 4-8 hours, and complete molding and sintering under the combined action of high temperature and high pressure; Step 4): after the heated reactor is cooled to room temperature, the sheath is removed to obtain a composite oxide formed object, the shape of which is consistent with the shape of the inner cavity of the sheath; Step 5): placing the molded product obtained in step 4) in an infrared heater for heating at a temperature of 100 to 600° C. for a holding time of 10 to 15 hours; Step 6): The molded product treated in step 5) is crushed to obtain composite oxide carrier particles of a desired mesh size.

2. The preparation method according to claim 1, characterized in that: The pore-forming agent in step 1) is selected from one or more of ammonium carbonate, ammonium bicarbonate, ammonium chloride and urea.

3. The preparation method according to claim 1 or 2, characterized in that: Step 1) the Al2O3 powder and M x O y The mass ratio of powder to pore-forming agent is 10-30:10-30:

1.

4. The preparation method according to claim 3, characterized in that: Step 1) the Al2O3 powder and M x O y The mass ratio of powder to pore-forming agent is 20:20:

1.

5. The preparation method according to claim 1 or 2, characterized in that: In step 2), the vacuum degree in the bag is 10 -1 ~10 -3 Pa.

6. Use of the composite oxide support prepared according to the preparation method according to any one of claims 1 to 5 in preparing a catalyst for selective hydrogenation of acetylene.

7. The use according to claim 6, characterized in that: The active component of the acetylene selective hydrogenation reaction catalyst is Pd.

8. The use according to claim 6, characterized in that: The acetylene selective hydrogenation reaction catalyst is prepared by the following method: immersing the composite oxide carrier in a Pd precursor solution, fully immersing so that the active material is fully adsorbed on the carrier, and then drying and reducing with hydrogen to obtain the acetylene selective hydrogenation reaction catalyst.

9. The use according to claim 7, characterized in that: The precursor of Pd is PdCl2.

10. Use of the acetylene selective hydrogenation reaction catalyst obtained according to claim 6 in acetylene selective hydrogenation reaction.

Citation Information

Patent Citations

  • Method for preparing Pd hydrogenation catalyst composite support

    CN106693988A

  • Highly dispersed palladium nanoparticle catalyst, preparation method and application thereof

    CN110508277A